Diabetic Foot Ulcers and Risk Fall in People with Type 2 Diabetes Mellitus in BLUD RSUD Dr. Ben Mboi Manggarai Regency, NTT - Ningsih, Oliva Suyen; Iwa, Kornelia Romana; Simon, Maria Getrida; Sinar, Kataria Anastasia (Jurusan Keperawatan FIKES UNSOED, 2021)
The prevalence of diabetes mellitus in Manggarai Regency in 2019 is 535 people and some of them have diabetic foot ulcers. Patients with diabetic foot ulcers had a higher risk of falling than others.This study was to determine the risk factors for diabetic foot ulcers and the risk of falls in patients with type 2 diabetes mellitus. A quantitative study using a cross-sectional study was conducted at BLUD RSUD dr. Ben Mboi Â in April-June 2020 (n = 51).The sampling technique used was purposive sampling with a questionnaire of diabetic foot screening and risk stratification form and Morse scale. Logistic regression results showed that there was a significant relationship between claudication (AOR: 8.409, 95% CI 1.664-42.500, p value 0.010), history of previous diabetic foot ulcers (AOR: 5,680, 95% CI 1,151-28,035, p value 0.033) with diabetic foot ulcers. There was a significant relationship between hypertension (AOR: 0.152, 95% CI 0.028-0.834, p value 0.030), diabetic foot ulcers (AOR: 11.392, 95% CI 1.277-101.651, p value 0.029) with the risk of falling for patients with type 2 diabetes mellitus. Â Assessment of the risk of diabetic foot ulcers and the risk of falls should be done in patients with diabetes mellitus with or without neuropathy peripheral